Optimization model for road grading to achieve full surface drainage of stormwater runoff in urban developments - Marwan Amin Mohamed Amin; Ashraf Hassan Mahib Ghanem; Yehya Emad Hamdy Hassan (2025)
This study presents a model, termed the Surface Drainage Optimal Road Grading (SDORG) model, designed to optimize road grading for full surface drainage of stormwater runoff in urban developments. Traditional stormwater drainage systems primarily rely on gravity pipe networks, which often require frequent maintenance and may not be sustainable or cost-effective in the long term. In contrast, surface drainage systems, incorporating road grading and green infrastructure such as permeable pavements, swales, and rain gardens, offer more sustainable alternatives. The SDORG model focuses on optimizing road intersection elevations and flow paths to ensure that roads function as open channels, directing stormwater toward the development boundaries. The model utilizes the Rational method for peak discharge estimation, the Manning$1 (Bs equation for road gutter capacity, and a Genetic Algorithm for optimization. It operates on two levels: determining optimal finished road levels at road intersections and establishing optimal flow paths to minimize construction costs while adhering to hydraulic and geometric constraints. The SDORG model was validated through multiple scenarios, confirming its efficiency in minimizing construction costs and ensuring full surface drainage of stormwater runoff. The results also affirm its importance as a reliable design tool that provides cost-effective and sustainable road grading solutions in urban developments.s
(3Jbhe gPg GdOQGSI HJbOje fehPL GdJUeje GdCeKd dJUQja ejGg GdCeWGQ YHQ GdWQb GdSWMjI (B(SDORG)(3, hGdPj jgOa Edi JYjjf GfMOGQ GdWQb dVeGf JUQja cGed dejGg GdCeWGQ aj GdefGWb GdMVQjI HTcd Gef(B. (3JYJeO CfXeI JUQja ejGg GdCeWGQ GdJbdjOjI HTcd QFjSj Ydi THcGJ CfGHjH GdLGPHjI, hGdJj ZGdkHG eG JJWdH UjGfI eJcQQI hbO dG Jchf eSJOGeI Ch aqYGdI ef MjK GdJcdaI Ydi GdeOi GdWhjd(B. (3Ydi GdfbjV ef Pdc, JbOe CfXeI GdJUQja GdSWMj, GdJj JOeL JUeje GdWQb eY GdHfjI GdJMJjI GdNVQGA eKd GdCQUaI GdbGHdI ddfaGP, hGdMOGFb GdeWQjI, HOGFd CcKQ GSJOGeI(B. (3jQcR fehPL (B(SDORG) (3Ydi JYjjf GQJaGYGJ JbGWYGJ GdWQb hJMOjO eSGQGJ GdJOab dVeGf Cf JYed GdWQb cbfhGJ eaJhMI, JhLg ejGg GdCeWGQ fMh MOhO GdJWhjQ(B. (3jSJNOe GdfehPL GdWQjbI GdefWbjI dJbOjQ GdJOabGJ GdbUhi, heYGOdI eGffL dJYjjf bOQI JUQja GdWQb, HGdEVGaI Edi GdNhGQRejI GdLjfjI dJMbjb GdJMSjf GdCeKd(B. (3hjYed GdfehPL Ydi eSJhjjf(B: (3JMOjO GdGQJaGYGJ GdeKdi dJbGWYGJ GdWQb hJMOjO eSGQGJ GdJOab GdeKdi dJbdjd JcGdja GdHfGA eY GdGdJRGe HGdbjhO GdgjOQhdjcjI hGdgfOSjI(B. (3Je GdJMbb ef caGAI GdfehPL aj Jbdjd JcGdja GdGfTGA hJMbjb JUQja cGed dejGg GdCeWGQ GdSWMjI, eeG jDcO CgejJg cCOGI JUeje ehKhbI JSge aj JhajQ Mdhd GbJUGOjI heSJOGeI dJShjGJ GdWQb HGdefGWb GdMVQjI(B.s
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 169-171.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Rainwater drainage; (3UQa ejGg GdCeWGQ s; Urban Stormwater Management -- Road Grading -- Surface Drainage Optimization -- Genetic Algorithm -- Sustainable Infrastructure -- Urban Stormwater Systems